Дериваційний потенціал дієслів-ономатопів на позначення супровідного звуковияву у процесі споживання: (зіставний аспект наповнення субстантивної зони типових словотвірних парадигм відзвуконаслідувальних дієслів в українській і польській мовах) - Kushlyk, Oksana (Theoria et Historia Scientiarum, 2024)
The article highlights the role of the stem as a typologizing factor in studying Ukrainian and Polish word formation. The object of attention is sound-imitating verbs that stand for the accompanying sounds produced in the act of food intake as a daily physiological human need. Based on the word-formation-paradigmatic principle of systematizing the factual material, adequate to the base-centric aspect of derivatology development in Slavic languages, the author structures deverbative found in both languages by morphological zones, clarifies the continuum of semantic positions realized by deverbatives within substantive morphological zone, determines a set of word-forming means as explicators of these semantic positions, motivates the nature of semantic relations between the semantic structure of the stem and derived words in order to predict the further development of the semantic structure of the stem, identifies the factors that activate or, conversely, slow down the word-forming capacity of top verbs, and on this basis establishes the word-forming potential of sound imitating verbs that indicate the accompanying sounds produced in the act of food intake and appraises the degree of functional correspondence of the described word-forming phenomena in Ukrainian and Polish as genetically related languages.